Katedra Prawa Konstytucyjnego — historia - Ławniczak, Artur; Preisner, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This part of the Faculty of Law at the Polish University of Wrocław has existed in many onomastical and organizational variants from 1946 up to our days with official perspectives for future. Our department is of great importance both in the educational process as well in scientific research. It is necessary to mention count Andrzej Mycielski as a founder of this structure and educator of his successors. One of these persons, namely assistant professor Aleksander Patrzałek headed the Department from 1971 and was lately also the Dean of the Faculty. We can sea in the Lower Silesian “Quarter Latin” signs of his activity in the form of buildings constructed for the students of law, administration or economy and for their teachers. In 1996 a formal leadership of the Department is taken over by Prof. Kazimierz Działocha, known for his membership in Constitutional Court, Senate and Legislative Council. He was also one of the “fathers of the new constitution” and the coordinatorof great theoretical description of Magna Charta from 1997. In the 21st century, from 2002, his successor to the position of the Department’s head was Prof. Bogusław Banaszak — very eminent in the field of international academic cooperation and Doctor Honoris Causa of many universities from abroad. At present, he is the Dean of the Law and Administration Faculty in Zielona Góra, and as a consequence from 2014 Mariusz Jabłoński has been head of the Department.
Keywords: Katedra Prawa Konstytucyjnego; Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego; historia